1997
DOI: 10.1161/01.str.28.9.1660
|View full text |Cite
|
Sign up to set email alerts
|

IgG Anticardiolipin Antibody Titer >40 GPL and the Risk of Subsequent Thrombo-occlusive Events and Death

Abstract: Our data suggest that subsequent thrombo-occlusive events and death after focal cerebral ischemia associated with IgG aCL may occur sooner and more frequently with GPL > 40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(110 citation statements)
references
References 29 publications
5
96
1
8
Order By: Relevance
“…696 A limited number of studies have examined the effect of antiphospholipid antibodies specifically on the risk for recurrent thromboembolic events after an initial TIA or stroke. [697][698][699] In the only study to exclusively enroll young adults <50 years of age, antiphospholipid antibodies were associated with increased risk for recurrent stroke or venous thromboembolism. 700 Other studies that enrolled older patients or a mixture of young and old patients with ischemic stroke indicated wide variability in the prevalence of antiphospholipid antibodies, from 6% to 46%, and inconsistent findings for an association.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…696 A limited number of studies have examined the effect of antiphospholipid antibodies specifically on the risk for recurrent thromboembolic events after an initial TIA or stroke. [697][698][699] In the only study to exclusively enroll young adults <50 years of age, antiphospholipid antibodies were associated with increased risk for recurrent stroke or venous thromboembolism. 700 Other studies that enrolled older patients or a mixture of young and old patients with ischemic stroke indicated wide variability in the prevalence of antiphospholipid antibodies, from 6% to 46%, and inconsistent findings for an association.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…700 Other studies that enrolled older patients or a mixture of young and old patients with ischemic stroke indicated wide variability in the prevalence of antiphospholipid antibodies, from 6% to 46%, and inconsistent findings for an association. [690][691][692][693][694][696][697][698][699]701 The wide variability reflects differences in diagnostic criteria, including persistence.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Early studies showed an increased recurrent stroke risk associated with aPLs, 24,25 but later studies that included larger numbers of patients failed to find such an association. 8,26 The Antiphospholipid Antibodies and Stroke Study (n=1770), a prospective cohort study, reported that immunoreactivity to either aCL or lupus anticoagulant antibodies at the time of a first ischemic stroke did not influence the risk of subsequent thrombo-occlusive events over the following 2 years.…”
Section: November 2016mentioning
confidence: 99%
“…Patients were prospectively followed to estimate the effect of aCL titer on time to and risk of subsequent thrombo-occlusive events (stroke, transient ischemic attack, deep venous thrombosis, pulmonary embolism, myocardial infarction) and death. Patents with aCL titers > 40 GPL were younger, had more prior strokes, more frequent subsequent thrombo-occlusive events and death, and a shorter median time to event (Levine et al, 1997). The more recent study performed in 432 Taiwanese adults with cerebral ischemia disclosed an interesting impact of aCL IgG.…”
Section: Relationship Between Antiphospholipid Antibodies and Atherosmentioning
confidence: 97%